Long‐term efficacy and complications of a multicentre randomised controlled trial comparing retropubic and transobturator mid‐urethral slings: a prospective observational study. (6th October 2021) - Offiah, I; Freeman, R; ,
Abstract : Objective: There are concerns regarding the risks of mid‐urethral slings (MUS) for stress urinary incontinence (SUI), particularly because of the lack of long‐term data. We compare patient‐reported outcomes of a multicentre randomised controlled trial of retropubic (TVT, GYNECARE™) versus transobturator (TOT, MONARC™) tape surgery at 12 years. Design and setting: A multicentre study was performed in 11 tertiary referral centres. Population: A cohort of 180 participants from the original trial, the majority of whom had mixed urinary incontinence. Methods: Postal questionnaire survey of patient‐reported outcome measures using the International Consultation on Incontinence Questionnaire, Patient Global Impression of Improvement questionnaire (PGI‐I) and a numeric rating scale pain questionnaire. Main outcome measures: Comparison of the efficacy and complications between the TVT and TOT procedures in the long term. Results: A total of 110/180 responses were received: 55 for TVT and 55 for TOT. The mean follow‐up was 12.8 ± 0.29 years (SD). TVT was significantly superior to TOT: 41.8% TVT with no SUI, versus 21.8% TOT ( P  = 0.04). Urgency urinary incontinence (UUI) was the most bothersome urinary symptom: 14.5% of respondents reported UUI after TVT and TOT. This was an improvement from the baseline levels: 61.8% TVT and 76.4% TOT. Seventeen patients (9 TVT and 8 TOT) out of 121 reported moderate or severe pain with severe pain in 3 with TVT and 2 with TOT. Overall, 80% TVT and 77% TOT participants reported their symptoms as improved on the PGI‐I. Conclusions: TVT is superior to TOT for SUI cure. Efficacy is reduced by 12 years. There is low incidence of severe vaginal or groin pain. Careful patient counselling on long‐term outcomes is required. The Retropubic tape appears to be an effective treatment for the majority of women with SUI. Tweetable abstract: Retropubic tape has superior efficacy to transobturator tape. Complications are comparable with low rates. Tweetable abstract: Retropubic tape has superior efficacy to transobturator tape. Complications are comparable and uncommon.